Mobile applications as an aid in treating obese and overweight people - Gutowska, Marika; Belcarz, Wiktoria; Fijałek, Paulina; Kalinowska, Karolina; Karczmarz, Jan; Kosińska, Agnieszka; Orzechowska, Joanna; Orzechowski, Michał; Paprocka, Aleksandra; Świrk, Urszula (Quality in Sport, 2025)
Apps use can benefit to improve body weight, body mass index and body fat percentage. The effectiveness is increasing with the older age and duration of the intervention. Using Ai assisted app can improve overeating habits, snacking habits, immediate thinking, self-regulation, depression and physical activity with no improvement of the anxiety. App users are more likely to attend health check. Early app engagement and self reported dietary adherence are predictors of weight loss. By using machine learning and an app it is possible to identify and predict weight loss trajectories. Combining the use of the app with the new technologies (smart band, glucose monitor, motion based classifier) benefits in weight loss, improve body composition, physical activity and provide complementary information. Adding push notifications as a feature of mobile apps have positive impact in body composition variables. Mobile health intervention can help women with obesity to manage their gestational weight gain, body weight before childbirth and newborns birth weight. It may also help reduce caesarian section rate and increase physical activity of pregnant women. Adding a digital intervention to standard care increases it efficiency. Mobile apps for parents can be helpful in reducing childhood obesity by reducing consumption of sweet and salty treats, sweet drinks. Most important information that app should be conveying are feeding tips and recipe content, while the most desirable features where that which allowed tracking child growth and setting feeding goals. In some research mobile apps appeared to be ineffective in increasing physical activity and improving diet in adolescents, while in the other quite the opposite. The lack of effectiveness in the studies selected in this review was probably due to low adherence to the research program and small groups. The deficits in initiating application are a negative predictor of attrition in adolescents.